Impact of intracystic ethanol instillation on ovarian cyst diameter and adjacent ovarian tissue - Atilgan, Remzi; Ozkan, Zehra Sema; Kuloglu, Tuncay; Kocaman, Nevin; Baspinar, Melike; Can, Behzat; Sapmaz, Ekrem (Elsevier Science Bv, 2014)
Objective: To investigate the regression level of simple ovarian cyst size after local ethanol application and the damage level of adjacent ovarian reserve in rats. Study design: This study was conducted at Firat University Animal Laboratory with 18 mature (12-14 weeks old) female Wistar albino rats weighing 200-220 g, with regular cycles. Ovarian cyst induction was performed with unilateral salpingectomy. Fourteen rats with ovarian cysts after a second laparotomy were divided into two groups as follows: Group 1 (n = 7): cyst aspiration group, and Group 2 (n = 7): intracystic 95% ethanol application group. One month after the cyst aspiration procedure a third laparotomy was performed. The cyst number and size were recorded for each rat. Right ovariectomy was performed and formalin-fixed/paraffin-embedded tissues were sectioned at 51 mu m thickness. Under light microscopy, ovarian total follicle reserve and fibrosis were evaluated with Masson trichrome staining and apoptosis was evaluated with TUNEL staining. The groups were compared with the Mann-Whitney U test and Wilcoxon Rank test. p < 0.05 was considered significant. Results: Ovarian cyst formation was observed in 85% (15/18) of rats. The mean diameter of ovarian cysts in Groups 1 and 2 were, respectively, 10.3 mm and 10.1 mm. After aspiration, there was no significant reduction in the cyst diameter (10.3 mm vs 8.1 mm), but after ethanol application the diameter significantly reduced (10.1 mm vs 3.4 mm, p < 0.05). Mean ovarian follicle count in Group 2 was significantly lower than in Group 1 (25 vs 42, p < 0.05), and mean fibrosis and apoptosis scores in Group 2 were significantly higher than in Group 1 (2.5 vs 0.9, p < 0.05). Conclusion: Local ethanol application reduces cyst diameter but concomitantly decreases ovarian reserve due to increased fibrosis in rats. In humans, intracystic ethanol application should be performed cautiously. (C) 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: Ethanol sclerotherapy; Ovarian reserve; Salpingectomy; Apoptosis